PENGARUH PENDIDIKAN ORANG TUA DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR BAHASA INGGRIS SISWA (SURVEY PADA SD NEGERI DI KABUPATEN LEBAK) - Samsu Bahri (STKIP Setiabudhi, 2019)
This study aims to analyze the truth of the hypothesis regarding the influence of reading interest and vocabulary mastery on the ability to write text description students. The research hypotheses tested included: 1) The Effect of Parental Education and Learning Motivation on students' English learning achievement. 2) the effect of parental education on students' English learning achievement. 3) The effect of learning motivation on students' English learning achievement. The research method used is observation. The population of this study was all grade VI students of SD Negeri in Lebak Regency with a sample size of 60 students, with a simple random sampling technique. Instrument data about parental education and learning motivation obtained through questionnaires and English learning achievement were obtained from report cards. Data analysis uses multiple regression analysis. The results of hypothesis testing obtained the following conclusions: (1) there is a significant influence of parental education and learning motivation on the learning achievement of English students in class VI at SD Negeri Regency Lebak. This is evidenced by the value of sig. = 0,000 <0.05 and t arithmetic = 55.905. (2) there is a significant influence of learning motivation on English language learning achievement of Grade VI students of SD Negeri in Lebak Regency. This is evidenced by the value of sig. = 0,000 <0.05 and t arithmetic = 5.926. (3) there is a significant influence of learning motivation on English language learning achievement of Grade VI students of SD Negeri in Lebak Regency. This is evidenced by the value of sig. = 0.001 <0.05 and t arithmetic = 3.570. Keywords: Parental Education, Learning Motivation, English Learning Achievement